Risolvere senza la tecnica X SOSTITUZIONE.
Spiegare i passaggi.
Per parti.
fattore finito $ f(x) = x \; ⇒ \; f'(x) = 1 $
fattore differ. $ g'(x) = (x-3)^{\frac{1}{2}} \; ⇒ \; g(x) = \frac{2}{3} (x-3)^{\frac{3}{2}}$
per cui
$ = \frac{2}{3} (x-3)^{\frac{3}{2}} - \frac{2}{3}\int_3^4 (x-3)^{\frac{3}{2}} \, dx = $
$ = \left. \frac{2}{3} (x-3)\sqrt{x-3} - \frac{2}{3} \frac{2}{5}(x-3)^{\frac{5}{2}} \right|_3^4= $
$ = \left. \frac{2}{3} (x-3)\sqrt{x-3} - \frac{2}{3} \frac{2}{5}(x-3)^2 \sqrt{x-3} \right|_3^4= $
$ = \left. \frac{2}{15} (x-3)\sqrt{x-3} (5x- 2(x-3)) \right|_3^4= $
$ = \left. \frac{2}{15} (x-3)\sqrt{x-3} (3x+6) \right|_3^4= $
$ = \frac{2}{15} (4-3)\sqrt{4-3} (12+6) - 0 = $
$ = \frac{12}{15} $